O autoconhecimento da alma em Tomás de Aquino - Andrade, Marcelo Pereira de (2013)
Augustine makes the double distinction between the self of the mind: one, understood as an inner experience, intimate and immediate, the other, understood as a definition of the nature of mind achieved in the truth itself. Thomas Aquinas, dealing with the problem of the self-knowledge of the soul, resumes the distinction made by Augustine, but within a gnoseology of Aristotelian inspiration, in which the soul is conceived as a form of communicating the act of being to the body, but supposing it to obtain the necessary material for knowledge. Thus does Thomas Aquinas move away from Augustine when it comes to the self-knowledge immediate and originary from the soul